PENGALAMAN KOMUNIKASI TERAPEUTIK PEREMPUAN INDONESIA DALAM MENGGUNAKAN DAUN SIRIH - Ditha Prasanti; Puji Prihandini (Universitas Bina Sarana Informatika, 2018)
In communication techniques, we recognize the existence of therapeutic communication techniques that are usually used as one method or way that can encourage the healing process for individuals. In this case, researchers are interested in lifting the phenomenon of therapeutic communication experience experienced by Indonesian women in using betel leaf as a traditional medicine. Betel leaf as one of the herbal medicines believed to efficacious treat some diseases. In the digital era today, there are still Indonesian women who use the betel leaf as a traditional medicine to cure the disease. Researchers want to know several things, namely: (1) The reason why Indonesian women still believe in using betel leaf as a traditional medicine; (2) The experience of therapeutic communication of Indonesian women in using betel leaves as traditional medicine. This research uses qualitative approach with phenomenology method. The results of this study indicate that the reason why Indonesian women who still believe in using betel leaf as traditional medicine consists of because motives and in order to motives. The therapeutic communication experience of Indonesian women in using betel leaves includes verbal messages obtained through word of mouth and experienced directly through the therapeutic communication phase. Keywords:Experience of Communication, Woman, Betel Leaf, Traditional Medicine